Early menopause and a low body mass index are associated with an increased risk of coronary heart disease in Japanese women. Issue 7 (July 2022) - Yamanouchi, Keiko; Ohta, Tsuyoshi; Konta, Tsuneo; Nakamura, Fumihiro; Horikawa, Shouta; Nakai, Nanako; Sakai, Kazuyoshi; Fukase, Mika; Seino, Manabu; Yamatani, Hizuru; Watanabe, Masafumi; Ueno, Yoshiyuki; et al.
Abstract: Objective: The primary objective was to investigate the association between early menopause and cardiovascular disease (CVD) prevalence in Japanese women. The secondary objective was to ascertain the association with CVD risk factors. Methods: In this cross-sectional study, 7, 239 naturally menopausal women from the Yamagata Cohort Study who completed an annual health visit and questionnaire between 2009 and 2015 were divided into three groups according to their age at menopause (women experiencing menopause at <45, 45-49 y, and ≥ 50 y). The diagnosis of coronary heart disease (CHD) and stroke were made by self-report, while hypertension, hyperlipidemia, and diabetes mellitus, were diagnosed by vital signs and laboratory parameters. Logistic regression analysis was used to estimate the associations between age at menopause and CVD prevalence and CVD risk factors. Results: A total of 354 (4.9%) and 156 (2.2%) women reported a history of CHD and stroke, respectively. Women experiencing menopause at <45 years had a higher prevalence of CHD than those experiencing menopause at ≥50 years (OR 1.77, 95% CI 1.07-2.90; P = 0.023). Stroke, hypertension, diabetes mellitus, and hyperlipidemia were equally prevalent among the three groups. Significant interactions were observed between age at menopause and body mass index (BMI) ( P = 0.025) and parity ( P = 0.025). Among those with a BMI < 18.5 or parity ≥2, women experiencing menopause at <45 years had a significantly higher prevalence of CHD than those experiencing menopause at ≥50 years. Conclusion: Early menopause and low BMI were associated with CHD in Japanese women.